2016
DOI: 10.11005/jbm.2016.23.4.199
|View full text |Cite
|
Sign up to set email alerts
|

Health-related Quality of Life in Accordance with Fracture History and Comorbidities in Korean Patients with Osteoporosis

Abstract: BackgroundThe purpose of this study was to explore health-related quality of life (HRQOL) among Korean patients with osteoporosis and to measure the impact of fractures and comorbidity on their quality of life (QOL) using the Korean National Health and Nutrition Examination Survey (KNHANES) data with a nationwide representativeness.MethodsThis study was based on 4-year-data obtained from the KNHANES 2008 to 2011. Osteoporosis was diagnosed in 2,078 survey participants according to their bone mineral density me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…The main factor for low HRQOL in patients with osteoporosis is osteoporosis-related fractures, particularly vertebral fractures. [ 31 32 ] However, there is a paucity of data regarding osteoporosis with HRQOL in COPD patients. Osteoporosis-related fractures may play an important role in poor HRQOL in COPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The main factor for low HRQOL in patients with osteoporosis is osteoporosis-related fractures, particularly vertebral fractures. [ 31 32 ] However, there is a paucity of data regarding osteoporosis with HRQOL in COPD patients. Osteoporosis-related fractures may play an important role in poor HRQOL in COPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported a decrease in HRQOL among patients with knee osteoarthritis . Other studies have identified previous spinal fractures and comorbidities as factors associated with low health utility . Guillemin et al showed that a higher number of comorbidities was associated with a reduced HRQOL.…”
Section: Discussionmentioning
confidence: 99%
“…(35,36) Other studies have identified previous spinal fractures and comorbidities as factors associated with low health utility. (37,38) Guillemin et al (38) showed that a higher number of comorbidities was associated with a reduced HRQOL. These reports supported our findings that the existence of knee osteoarthritis and multiple comorbidities reduced HRQOL, Regardless of of denosumab treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis and OFs (i.e., DRFs, HFs, spine, and humerus fractures) are becoming more important health problems in the elderly [13]. OFs reduce quality of life and cause medical expenses in the elderly [14,15].…”
Section: Discussionmentioning
confidence: 99%